Effectively suppressed reflected photonic spin Hall effect - Sheng Lijuan; Xu Zixiao; Cao Yong; Tan Yawei; Ling Xiaohui; Zhou Xinxing (Nanophotonics)
The photonic spin Hall effect can engender transverse spatial and angular displacements in both transmission and reflection, with significant applications in optical imaging, edge detection, and the development of spin-based nanophotonic devices. While previous research has focused on enhancing the photonic spin Hall effect, suppression can be beneficial for photonic spin-switching, offering advantages such as increased speed and sensitivity in nanophotonic devices. In this study, we establish a quantitative correlation between the reflection coefficient and the transverse spatial and angular displacements of reflected light, as induced by the photonic spin Hall effect, grounded in electromagnetic theory. We find that the transverse spatial displacement of reflected light can be eliminated under the condition r pp = −r ss, where r denotes the reflection coefficient, and the first (second) superscript denotes the polarization of the reflected (incident) light. This condition applies to light with arbitrary polarization states, at arbitrary incident angles, and is independent of wavelength and beam waist. A similar outcome is obtained for the transverse angular displacement of the reflected light. Such distinctive displacements are attainable through the use of an electromagnetic interface that satisfies the reflected condition r pp = −r ss. Additionally, we provide a succinct overview of the methodologies for constructing reflective spin switches.